Development of E-Modules Based on the ICARE Learning Model to Improve Students' Creative Thinking and Scientific Communication Skills - Filda Mawaddah; Usmeldi (Postgraduate, University of Mataram, 2024)
This research aims to develop E-module teaching materials based on the ICARE learning model to improve high school students' creative thinking and scientific communication skills. The research method used in this research is the plomp model. The Plomp model consists of three stages, namely preliminary research, development or prototyping phase, assessment phase. Validation test using Aiken's V and Practicality formula. The results of the E-module validity test based on the ICARE learning model carried out by three validator experts obtained valid criteria, so that the e-module is suitable for use in learning activities. The teacher's practicality obtains very practical criteria, the students' practicality is in the very practical category. So, e-modules are very suitable for use in learning activities. E-modules based on the ICARE learning model have proven capable of improving high school students' creative thinking and scientific communication skills. The aim of this research is to see the practicality of e-modules based on the ICARE learning model to improve students' creative thinking and scientific communication skills.